Mediated lives : memory and construction of history in the Caribbean diaspora - Adjaye, Joseph K. (2005)
Argues that evocation of the Caribbean past resides not just in colonial records, books, official records, court records, administrative diaries, and other official records, but in particular, in popular memory, textualized through legend, myths, tales, rituals, song, institutionalized commemorations, and other mediations of the past constructed from the ground up.